Campur Kode Ceramah Ustadzah Mumpuni Handayani: Analisis Sosiolinguistik - Intan Ayu Linda; Siti Rumilah (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2020)
This study aims to determine the use of code mixing in the video study of Ustazah Mumpuni Handayayekti by using the analysis of sociolinguistic theories. The results of this study are using mixed code in lecturing Ustadzah Mumpuni Handayayekti into the use of: (1) mixed code of Javanese word forms, (2) mixed code of Javanese clause form codes, (3) mixed code of Balinese word forms, and (4) mixed code phrase of Javanese language. In addition, mixing the code out on the use (1) mixed form codes for Arabic clauses, (2) mixed form codes for Arabic words, (3) mixed form codes for Arabic phrases, and (4) mixed form codes for Indonesian words. Mixing the code in and mixing the code out used by Ustadzah Mumpuni Handayayekti in his lecture, shows that he is a multilingual speaker and can use variations of language well in the right context.